1997
DOI: 10.1038/ki.1997.214
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β1 and renal injury following subtotal nephrectomy in the rat: Role of the renin-angiotensin system

Abstract: Transforming growth factor-beta (TGF-beta) and the renin-angiotensin system (RAS) have both been implicated in the pathogenesis of chronic renal disease. The present experiment investigated the chronology of TGF-beta 1 gene expression following subtotal nephrectomy (STNx) in the rat and the effect of blocking the RAS by angiotensin converting enzyme (ACE) inhibition or by angiotensin II receptor (AT1) antagonism. Rats that had undergone subtotal nephrectomy developed hypertension, proteinuria, renal impairemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
171
4
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(191 citation statements)
references
References 54 publications
13
171
4
3
Order By: Relevance
“…Studies have shown that the protection from progressive renal injury afforded by ARB treatment initiated early after five-sixths nephrectomy is associated with normalization of glomerular capillary hydraulic pressure, suppression of proinflammatory gene induction, and macrophage infiltration. 9,10 These data provided support for the hypothesis that after extensive renal mass ablation, expression of ED-1, MCP-1, or ICAM-1 in high numbers of cells in the remnant kidney contributes to progressive renal injury. Although ARB was effective in preventing or attenuating upregulation of several proinflammatory genes in this model, additional interventions that specifically inhibit proinflammatory gene expression may lead to increased therapeutic options for patients with established chronic renal disease progression.…”
Section: Discussionsupporting
confidence: 66%
“…Studies have shown that the protection from progressive renal injury afforded by ARB treatment initiated early after five-sixths nephrectomy is associated with normalization of glomerular capillary hydraulic pressure, suppression of proinflammatory gene induction, and macrophage infiltration. 9,10 These data provided support for the hypothesis that after extensive renal mass ablation, expression of ED-1, MCP-1, or ICAM-1 in high numbers of cells in the remnant kidney contributes to progressive renal injury. Although ARB was effective in preventing or attenuating upregulation of several proinflammatory genes in this model, additional interventions that specifically inhibit proinflammatory gene expression may lead to increased therapeutic options for patients with established chronic renal disease progression.…”
Section: Discussionsupporting
confidence: 66%
“…TGFj91 influences ECM in several ways, including increasing ECM synthesis, decreasing ECM degradation and modulating the interaction between ECM and neighboring cells. There is substantial evidence to support a pathogenic role for TGF/91 in promoting the accumulation of ECM, leading to fibrosis and renal dysfunction in several models of experimental glomerular injury and human kidney diseases (27)(28)(29)(30). The report of TGF91 transgenic mice developing glomerulosclerosis indicates a causal relationship between TGF/91 and renal fibrosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…Other reports suggest that tubular atrophy and interstitial fibrosis may be induced by increased protein content of ultrafiltrate, giving rise to an inflammatory reaction and interstitial fibrosis (20,21). Upregulation of TGF-ß is consistently associated with these postglomerular events, irrespective of the proposed model of pathogenesis (22)(23)(24).…”
Section: Reevaluating Paradigms Of Renal Disease Progressionmentioning
confidence: 99%